2010
DOI: 10.1007/s10806-010-9255-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Care in Agriculture: A Social Perspective

Abstract: At its beginning, the European Union's Common Agricultural Policy (CAP) did not include measures to guide farmers in preserving ecosystems. At the same time, the social context on the 1960s and 1970s did not encourage environmental care to become a priority. Since the 1980s, new social concern expressed alarm over ecology, recognizing that agriculture can pollute. These social changes moved the CAP to add measures that linked agriculture and environment. In order to study if the EU decision-makers have designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…The interactions between the goods and services provided by rural areas are complex due to the trade-offs between them. Thus, the fact that the demand for multifunctionality is diffuse may lead to an insufficient provision of certain goods and services derived from agricultural activity, such as those related to the conservation of the environment [24]. Also, given that rural land is a limited resource, it may be that public policies enhance certain functions to the detriment of others according to the development model chosen for it [25].…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between the goods and services provided by rural areas are complex due to the trade-offs between them. Thus, the fact that the demand for multifunctionality is diffuse may lead to an insufficient provision of certain goods and services derived from agricultural activity, such as those related to the conservation of the environment [24]. Also, given that rural land is a limited resource, it may be that public policies enhance certain functions to the detriment of others according to the development model chosen for it [25].…”
Section: Introductionmentioning
confidence: 99%
“…It attempts to break the divide between conservation and agriculture. As some scholars have pointed out, the divide between agriculture and conservation is detrimental to the advancement of both livelihoods and conservation (see also Fay & Michon, 2005;Kereiva et al, 2007;Melania & Sayid, 2011;Scherr & McNeely, 2003). The piloting of agri-environmental management initiatives in places such as Zambia should thus be seen in the context of a strong push in much of the sustainable development literature for conservation solutions that posit a win-win solution for both livelihoods and conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Non -productive land measures for the preservation of the rural environments and enhancement of biodiversity. Also provide water-shed protection, carbon-sequestration, soil protection, pollination services and aesthetic services Source: World Bank, 2008;Baudron et al, 2007;Borsotto et al, 2008;EU, 2005;Dumanski et al, 2006;EU, 2005;Goman et al, 2001. This shift towards agri-environmental management implies that agriculture areas must be viewed as multi-functional landscapes which do not only produce food and fibres, but also various ecosystem services being demanded by society (Gorman et al, 2001;Melania & Sayid, 2011;Milestad et al, 2011;Pretty et al, 2003). The idea of extending conservation to agricultural landscapes heralds a new era of environmental conservationism and should be seen as a radical shift from the protected area thinking which viewed agro-landscapes as 'biological deserts' or a 'hostile matrix of isolated habitat fragments' (Batary et al, 2011(Batary et al, : 1894.…”
Section: Agri-environmental Management and Conservation Agriculturementioning
confidence: 99%
“…Previous research in various Mediterranean crops showed high erosion rates, and examples such as vineyards (Rodrigo-Comino, 2018), citrus (Cerdà, Morera, & Bodí, 2009), apricot (Keesstra et al, 2016), almonds (Wirtz, Seeger, & Ries, 2012), and persimmon orchards (Cerdà et al, 2016) are widely known. This is due to the Mediterranean climate and relief conditions, but also as a consequence of management that controls the soil cover (Sharma et al, 2017), which is some regions such as Andalusia (southern Spain) was not considered since the 1980s (Salazar-Ordóñez & Sayadi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in various Mediterranean crops showed high erosion rates, and examples such as vineyards (Rodrigo‐Comino, ), citrus (Cerdà, Morera, & Bodí, ), apricot (Keesstra et al, ), almonds (Wirtz, Seeger, & Ries, ), and persimmon orchards (Cerdà et al, ) are widely known. This is due to the Mediterranean climate and relief conditions, but also as a consequence of management that controls the soil cover (Sharma et al, ), which is some regions such as Andalusia (southern Spain) was not considered since the 1980s (Salazar‐Ordóñez & Sayadi, ). In this region, olive plantation show high runoff discharges with a high runoff peaks as was measured by several authors (e.g., Gómez, Romero, Giráldez, & Fereres, ; Martínez, Zuazo, & Raya, ), the largest olive oil‐producing region in the world.…”
Section: Introductionmentioning
confidence: 99%